Kuliah Kerja Nyata (KKN) during the Covid-19 Pandemic as a Form of Community Service - M. Ilham Lutfi (International Journal of Cultural and Social Science, 2020)
The pandemic not only presents anxiety about health threats, but alsothe welfare of many employees due to layoffs. Some of small, mediumand even large scale businesses were forced to go out of business.State Islamic University of North Sumatra immediately respondedpositively to the impact that emerged in the community due to theCovid-19 pandemic by holding Community DevelopmentParticipation to online with 4 theme "Awareness and concern for theCovid-19 outbreak, Relation of religion and health properly,religious moderation and Islamic da’wah education". With theStudent Creativity Program scheme KKN-DR and KKN- KS, studentsare expected to be able to actualize their ability to contribute toincreasing productivity and even people's income by providingeducation on how to do activities while adhering to health protocols,sharing knowledge on how to make products that are needed toprotect and increase endurance such as making masks from cloth,hand sanitizer and herbal drink. It is hoped that by sharing thisknowledge, people can remain productive and even open newbusinesses in terms of manufacturing these products to improve theireconomy. The method used is in the form of an explanation of how tomanufacture it along with the tools and materials needed for theproduct mentioned above. The process of making is uploaded tosocial media in the form of a video so that it can be accessed by thewider community. It is hoped that more and more people will remainenthusiastic, productive and even pursue the manufacturing businessof the above products to improve their economy and open up newjobs.